EFFECTS OF DIET COMPOSITION ON UNIFORMITY AT THE END OF THE CYCLE IN BROILER CHICKENS - Terraes, Juan Carlos (2011)
This paper describes the uniformity in broiler chickens, where the objective of thestudy was to evaluate two types of isocaloric diets with low and high protein level. Atotal of 195 broiler male chickens distributed in the two experimental groups were used.At the end of the production cycle (day 49), the uniformity for both diets were 68 ± 13% and 72 ± 12% respectively, and without statistical differences between groups throughoutthe production cycle or at the end of it. However, repeated measures analysis showedsignificant differences for uniformity, regardless of treatment (p<0.05), as there was amarked decrease in the variable of study towards the end of the first week (55%) ascompared to the initial value of 90%. The results indicate that despite the differences inchemical composition of the tested rations, both treatments showed similar percentagesof uniformity, and if considering the differences in costs due to the levels of protein in therations, it can be concluded that the lack of statistical differences between diets providesan important finding when considering the cost benefit analysis of production.